(3OhQ GdecJHI GdeOQSjI GdLOjO aj eSGfOI GdHQGeL GdJYdjejI aj HYV eOGQS HjQhJs - g ((3HjQhJs (3LGeYI GdbOjS jhSas, 2010)
(3JgOa GdOQGSI GdMGdjI Edi eYQaI eG gj GdecJHI GdeOQSjI heG gh OhQgG GdLOjO, heYQaI CKQ GdecJHI GdeOQSjI aj JfejI GdbOQGJ GdEHOGYjI YfO GdJdGejP, haj EZfGA eNRhfg GdacQj Hcd LOjO, heYQaI eG EPG cGf ddecJHI CKQ aYGd aj eSGfOI GdHQGeL GdJYdjejI, heG EPG cGf dCejf GdecJHI OhQ aj GdecJHI GdeOQSjI(B. (3EYJeOJ GdOQGSI Ydi GdefgL GdhUaj GdJMdjdj, ESJNOeJ GdGSJHGfI cCOGI dLeY GdHjGfGJ, ceG JVefJ GdOQGSI GdGSJeGQGJ hELQGA ebGHdGJ eY HYV GdeYdejf, hGSJNOeJ COGI GdRjGQI dcGaI GdecJHGJ GdeOQSjI GdJj TedJgG GdOQGSI(B. (3EbJUQJ gPg GdOQGSI Ydi eDSSGJ GdJYdje HeQMdJj GdKGfhj hGdeJhSW aj HjQhJ(B. (3acGfJ GdYjfI YThGFjI aJe GNJjGQ aFJjf ef GdeOGQS; GdaFI GdChdi Jedc ecJHGJ eOQSjI eWhQI, CeG GdKGfjI aJbJbQ Edi hLhO gPg GdecJHGJ; hbO HdZ YOO GdJdGejP (B24 (3JdejPkG h(B107 (3eYdekG heYdeI HGdEVGaI Edi (B14 (3CejfkG hCejfI ddecJHI(B. (3hNdUJ GdOQGSI HGdfJGFL GdJGdjI(B: 1) (3gfGc JaGhJ Hjf GdeYdejf hGdJdGejP aj LejY eOGQS HjQhJ, ceG Cf gfGc ecJHGJ aj LejY GdeOGQS GdJj JeJ RjGQJgG eeG jOd Ydi CgejJgG GdJQHhjI(B. 2) (3QcRJ GdJQHjI GdMOjKI Ydi eSGYOI GdJdejP ef CLd GdMUhd Ydi WQjbI efGSHI Jecfg ef eYQaI cja jWQM eTcdI hcja jMOOgG hcja jHMK Yf GdeUGOQ hGdeQGLY GdefGSHI GdJj JJYdb HgPg GdeTcdI(B. 3) (3Ef GdhGbY GddHfGfj aj eG jNU GdecJHGJ GdeOQSjI jNJda cKjQkG Yf GdfXQjGJ GdMOjKI(B. (3aGdecJHI dgG OhQ LOjO aj eSGfOI GdHQGeL GdJYdjejI hJKbja GdJdGejP, hdcf gPG GdOhQ djS aYGdkG aj GdYOjO ef eOGQS HjQhJ(B. (3aeG jRGd OhQ GdecJHI bGUQkG hgj eG JRGd HMGLI Edi GdeRjO ef GdJWhQ hGdeJGHYI(B.s
(3GdfhY (B: (3QSGdIs
Keywords: Beirut; Beyrouth; Librairie Scolaire; School Library; (3GdeOQSjIs; (3GdecJHIs; (3HjQhJs